1998
DOI: 10.1089/end.1998.12.493
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials Used in Urology: Current Issues of Biocompatibility, Infection, and Encrustation*

Abstract: This review focuses on the biomaterials used in urology, in particular, the properties of urethral catheters and ureteral stents currently being used in clinical practice. The importance of biomaterial type, biocompatibility, and encrustations are discussed and explained. Current management of bacterial infection and the importance of biofilms are presented, with recommendations based on published information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
84
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 147 publications
(87 citation statements)
references
References 59 publications
0
84
0
3
Order By: Relevance
“…For example, several studies reported that gram-negative bacteria adhered less to siliconized rubber than to other catheter materials. 4,72 Fig 1 shows a confocal microscopy image of a siliconized latex surface that had been incubated with E coli in broth for only 48 hours; a thick biofilm is clearly visible. Impregnating urinary catheters with antimicrobial agents, such as silver ions or nitrofurazone, 73 has also been attempted.…”
Section: Possibly Effective Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, several studies reported that gram-negative bacteria adhered less to siliconized rubber than to other catheter materials. 4,72 Fig 1 shows a confocal microscopy image of a siliconized latex surface that had been incubated with E coli in broth for only 48 hours; a thick biofilm is clearly visible. Impregnating urinary catheters with antimicrobial agents, such as silver ions or nitrofurazone, 73 has also been attempted.…”
Section: Possibly Effective Strategiesmentioning
confidence: 99%
“…2 A formal definition of biofilm includes 3 components: (1) adherence of the microorganisms, either to a surface or to each other; (2) a change in gene expression resulting in a different phenotype from the planktonic state; and (3) an extracellular matrix composed of host components and secreted bacterial products. 3,4 A functional definition of biofilm also includes the fact that biofilm results in chronic, persistent infections that are difficult to eradicate with antimicrobial therapy. 5 The relevance of biofilm to catheter-associated urinary tract infection (UTI) (CAU-TI) is that a foreign body, such as an indwelling urethral catheter, connecting a normally sterile, hydrated body site to the outside world will inevitably become colonized with microorganisms.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations